IDENTIFIKASI KAWASAN HUNIAN DI SEKITAR RUMAH SAKIT HARAPAN KITA DAN RUMAH SAKIT KANKERDHARMAIS, JAKARTA BARAT, INDONESIA - Muhammad Fawwaz Athallah Ramadhan; Rahel Situmorang; Herika Muhamad Taki (Jurnal Lingkungan dan Kota, 2023)
Harapan Kita Heart Hospital and Dharmais Cancer Hospital are national scale hospitals in Indonesia, are central hospitals with the most complete service facilities for heart disease and cancer. these two hospitals are referral centers for patients from various provinces and cities throughout Indonesia. There are various levels of care needed, patients must be accompanied by family or relatives at the time of treatment. For this reason, patients need a place to live around these two hospitals. The purpose of this study is to identify residential areas around Harapan Kita Heart Hospital and Dharmais Cancer Hospital, as well as identify land use suitability with the DKI Jakarta RDTR 2022. The study location is RT01 and RT 08, RW 06 and RW 09, South Bamboo City Village, Palmerah District, West Jakarta City, which is directly adjacent to the two hospitals. Descriptive analysis was used to determine the changes that occurred based on in-depth interviews with 30 study respondents who were boarding house owners or guards. The results showed a change in residential form by 80% from a onestory house to a 2.3-storey building, with the Basic Building Coefficient and Building Floor Coefficient not in accordance with the DKI Jakarta RDTR 2022.